On the effect of intramolecular H-bonding in the configurational assessment of polyhydroxylated compounds with computational methods. The hyacinthacines case. (15th February 2019) - Zanardi, María Marta; Sortino, Maximiliano A.; Sarotti, Ariel M.
Abstract: Hyacinthacines are important members of the pyrrolizidine family, with several compounds having ambiguous, revised or unverified structures. Herein we thoroughly explored the performance DP4 and DP4+ for the in silico stereoassignment of hyacinthacines A1, A2 and five synthetic isomers. The results suggested that the quality of the predictions strongly depended on the conformational landscape provided by DFT energies, with five compounds correctly assigned. In the two cases incorrectly classified we found that the source of the problem was conformational in nature, with spurious conformations being considerably over-stabilized by intramolecular H-bondings. We showed that neglecting such shapes resulted in a noteworthy improvement, with all compounds correctly assigned in high confidence (>99.9%). Graphical abstract: Image 1 Highlights: Hyacinthacines are important members of the pyrrolizidine family. Several hyacinthacines have ambiguous, revised or unverified structures. We explored DP4 and DP4+ in the stereoassignment of seven known hyacinthacines. The quality of the predictions strongly depended on the conformational preferences. Removing spurious conformations with intramolecular H-bonding improved the results.